Modelling and Characterization of Down-Conversion and Down-Shifting Processes for Photovoltaic Applications - Gabr, Ahmed (Université d'Ottawa / University of Ottawa, 2016)
Down-conversion (DC) and down-shifting (DS) layers are optical layers mounted on the top surface of a solar cell that can potentially increase the solar cell efficiency. The effect of DC and DS layers to enhance the performance of single-junction solar cells has been studied by means of simulation and experimental work. In this thesis a model is developed to study the effects of DC and DS layers by modifying the incident spectrum. The effect of the layers on ideal cells as well as commercial grade silicon and CIGS solar cells that are modeled in a device simulator is examined. Silicon nanocrystals (Si-nC) embedded in a silicon dioxide matrix to act as a DS layer were fabricated and characterized at McMaster University as part of this project. The measured optical properties as well as the photoluminescence measurements are used as input parameters to the optical model. The enhancement due to the Si-nC when coupled to silicon and CIGS solar cells is explored. Beside the DC and DS effects, there is also disturbance to the surface reflections due to the addition of a new layer to the top surface and is referred to as antireflection coating (ARC) effect. For the simulated silicon solar cell under the standard AM1.5G spectrum (1000W/m2), a maximum increase in Jsc of 8.4% is achieved for a perfect DS layer as compared to a reference cell, where 7.2% is due to ARC effect and only 1.2% is due to DS effect. On the other hand, there is an increase in Jsc of 19.5% for the CIGS solar cell when coupled to a perfect DS layer. The DS effect is dominant with 18%, while the ARC effect contributes only 1.5% to the total Jsc enhancement. Accurately characterizing DS layers coupled to solar cell requires knowledge of optical properties of the complete structure. Internal quantum efficiency is an important tool for characterizing DS systems, nevertheless, it is rarely reported. In addition, the ARC effect is not experimentally decoupled from the DS effect. In this work, a straightforward method for calculating the active layer contribution that minimizes error by subtracting optically-modeled electrode absorption from experimentally measured total absorption.
Keywords: Photovoltaics; Solar cell; Down-conversion; Down-shifting; Silicon nanocrystals; CIGS; Modelling; Quantum efficiency